The Effect of Dual Role Conflict and Workload on Female Employee Performance With Job Stress As An Intervening Variable (Study At PT. Bank Rakyat Indonesia, Jayapura Regional Office) - Ayu Leonita Kusumaningrum; Anita Maharani; Sahnaz Ubud (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Nowadays, women are forced to work as much as men because of the increasing demands to meet basic needs. As a result, the barriers between men and women in workplace positions are gradually being eliminated. Dual role conflict is a term used to describe the two roles played by women who work and have families at the same time. Women must be able to carry out both tasks effectively at the same time. This study has a sample of 230 employees of Bank BRI RO Jayapura. Based on the analysis that has been carried out in the study, it was found that the influence of dual role conflict and workload on employee performance with job stress as an intervening variable (Study at PT. Bank Rakyat Indonesia Regional Office Jayapura) has a positive and significant effect